2016
DOI: 10.1891/1058-1243.25.1.37
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering the Golden Veil: Applying the Evidence for Telephone Screening to Detect Early Postpartum Depression

Abstract: Postpartum depression (PPD) is often detected later than symptom onset, or even undetected, because of lack of prompt or adequate screening. An evidence-based PPD screening protocol using a telephonebased format within a primary care practice was developed to identify symptoms and initiate treatment between 2 and 3 weeks postpartum. The Edinburgh Postnatal Depression Scale was used, with positive screens referred for provider and support services, and then tracked for follow-through. Fifty-two percent of women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(25 citation statements)
references
References 38 publications
(47 reference statements)
0
21
0
4
Order By: Relevance
“…The majority of studies (n = 8) have been conducted in the United States. 28,39,41,43,[49][50][51][52] The remaining two investigations were from England 53 and Canada. 54 Most studies have included women older than 18 years of age, but four articles also recruited adolescent mothers.…”
Section: Sample Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…The majority of studies (n = 8) have been conducted in the United States. 28,39,41,43,[49][50][51][52] The remaining two investigations were from England 53 and Canada. 54 Most studies have included women older than 18 years of age, but four articles also recruited adolescent mothers.…”
Section: Sample Characteristicsmentioning
confidence: 99%
“…43,51,52,54 Regarding the period of interest, most investigations focused on postpartum (n = 8, 80 percent). 28,41,43,[49][50][51][52]54 Only two articles (20 percent) screened for depression during the prenatal period. 39,53 Also interestingly, we observed that the moment in which screening was conducted varied widely across investigations.…”
Section: Sample Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations